Cultural Studies Is The Ideal Introduction For Progressive Analytical View Of The Social Structures (Journal of Namibian Studies : History Politics Culture, 2023)
Culture' is an umbrella term which encompasses the social behaviour and norms found in human society, as well as the knowledge, beliefs, arts, laws , customs ,capabilities and habits of the individuals. Culture cannot be found if the individual lives in isolation. There should be overlapping, sharing of interests ,participation and mutual appreciation. People as a whole should try to learn and socialize to form and inculcate a better culture in society  .Presently to  facilitate the ideas and meanings of what culture means in the changing world , the philosophies on culture have become a serious discourse in the academic world , a mandatory part of the syllabus universally for higher studies which is termed as  Cultural Studies.